2018
DOI: 10.1177/1524838018757750
|View full text |Cite
|
Sign up to set email alerts
|

Physical Abuse, Emotional Abuse, and Neglect and Childhood Behavior Problems: A Meta-Analysis of Studies in Mainland China

Abstract: The relationship between three types of child maltreatment, including physical abuse, emotional abuse and neglect, and childhood behavior problems in Mainland China, has not been systematically examined. This meta-analysis reviewed findings from 42 studies conducted in 98,749 children in Mainland China and analyzed the pooled effect sizes of the associations between child maltreatment and childhood behavior problems, heterogeneity in study findings, and publication bias. In addition, this study explored cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 49 publications
(57 reference statements)
2
25
0
3
Order By: Relevance
“…The finding that traumatic emotional abuse was associated with DTD is consistent with extensive evidence that severe verbal or emotional abuse has complex psychobiological sequelae involving emotional, behavioral, and self-or relational dysregulation that extends beyond PTSD (Cui & Liu, 2020;Spinazzola et al, 2014). In the present study, emotional abuse was associated with both physical abuse or assault and family violence, raising a possibility that these three forms of victimization are a risk-factor caravan (Chen et al, 2015;Layne et al, 2014) for DTD.…”
Section: Discussionsupporting
confidence: 89%
“…The finding that traumatic emotional abuse was associated with DTD is consistent with extensive evidence that severe verbal or emotional abuse has complex psychobiological sequelae involving emotional, behavioral, and self-or relational dysregulation that extends beyond PTSD (Cui & Liu, 2020;Spinazzola et al, 2014). In the present study, emotional abuse was associated with both physical abuse or assault and family violence, raising a possibility that these three forms of victimization are a risk-factor caravan (Chen et al, 2015;Layne et al, 2014) for DTD.…”
Section: Discussionsupporting
confidence: 89%
“…The relationship between child physical abuse and behavior problems has been well documented in the literature across cultures (Fry et al, 2012;Gershoff et al, 2012;Pace et al, 2019). Consistently, a recent meta-analytic study of 42 studies in Mainland China also found that physically abused children manifested more externalizing behaviors (Cui and Liu, 2020). The link remains significant even after controlling for other forms of maltreatment (Renner and Boel-Studt, 2017;Muniz et al, 2019), and the effect of physical abuse practiced by mothers demonstrates more salient effect on externalizing behaviors than that practiced by fathers (Cui et al, 2018).…”
Section: Introductionmentioning
confidence: 69%
“…At the individual level, several studies show gender differences in different types of child abuse (Kumar et al, 2017;Salem et al, 2020); however, there has been no consistent conclusion internationally. Many studies found boys were more likely to experience physical abuse, compared with girls, and that a higher prevalence of neglect is observed among girls than boys (Cui and Liu, 2020;Wan et al, 2020). However, other studies found that boys were more likely to report being victims of emotional abuse and neglect than girls (Li et al, 2012), and there were also some studies reporting that there is no evidence of gender difference in associations (Stoltenborgh et al, 2012).…”
Section: Risk Factors Of Child Maltreatmentmentioning
confidence: 99%